Van Helsing the London assignment - Jackman, Hugh; Bridgeman, Sharon (Universal ; distributed in the Philippines by MagnaVision, 2004)
Deep in the heart of London, the sinister creature, Mr. Hyde, terrorizes the late-night streets in a haunting crime spree. With the city in a panic, the Knights of the Holy Order send Van Helsing into London with the mission of tracking down and capturing the evil Mr. Hyde.